The Requirements of Achieving Sustainable Competitive Advantage under Framework of Constructing Green Strategy for Business Organizations ( perceptual analytical study) - سعيد سناء عبد الرحيم (Journal of Economics and Administrative Sciences, 2013)
The aim of this research is to know how business organizations achieve competitive advantage ,and make it sustainable through constructing a green strategy ( friend to environment) which is reflected on sustaining their competitive advantages .The problem of this study is presented through trying to answer many thoughtful questions, the most important of them are: 1-Can business organizations today make green strategies supporting their competitive advantage? 2-Is there a framework or mechanism could be depended on by business organizations to manage strategic risks of losing their competitive advantage? The research has depended on analytical perceptual descriptive method in analyzing the essential dimensions of the relation between having sustainable competitive advantages sources and constructing a green strategy. The research has come out into developing some mechanisms can be used as good strategic theories ,which lead to sustainable competitive advantage, and test the validity of the theoretical assumption of this research; for the purpose of constructing an active model for green strategy capable of field application, and is reflected on organization behavior. The most important recommendations of this research are to make the organization pay attention to environment demands under framework of constructing green strategy through getting benefit of business opportunities based on environment and creating sustainable competitive advantages